Hydrodynamics of the Cylinder Rotating in the Unbounded Viscous Medium - Ed.A. Bulanov (Механика машин, механизмов и материалов, 2009)
It is shown, that at first a laminar flow around rotating cylinder with growth of Reynolds number passes into a pseudo-laminar flow, and then into a steady turbulent flow. The equations of averaged velocity, fluctuating parts of the velocity, turbulent friction for pseudo-laminar flow is obtained on the basis of Reynolds equations determination, for steady turbulent flow from scheme of Boussinesq-Prandtl turbulent exchange, which is carried out as a result of volume element rotating. The comparison of calculation results of resistance coefficient with experimental data of Theodorsen and Regier is depicted.